The Semidiscrete Damped Wave Equation with a Fractional Laplacian - Lizama-Yanez, C (American Mathematical Society, 2023)
In this paper we completely solve the open problem of finding the fundamental solution of the semidiscrete fractional-spatial damped wave equation. We combine operator theory and Laplace transform methods with properties of Bessel functions to show an explicit representation of the solution when initial conditions are given. Our findings extend known results from the literature and also provide new insights into the qualitative behavior of the solutions for the studied model. As an example, we show the existence of almost periodic solutions as well as their profile in the homogeneous case. © 2023 American Mathematical Society.